Gambaran Proses Mengampuni pada Individu yang Mengalami Pengasuhan Buruk Orangtua - Zagötö, Sri Florina Laurence; Sandjaja, Stefanus Soejanto (Noetic Psychology, 2013)
Abstract.This study aimed to obtain a complete picture and will complete the real state of the individual in his suffering, discovery of meaning, and the process of forgiveness that has been going on self nurturing individuals who have bad parents. This study used qualitative methods and consisted of three women with the varied subject of different ages. The study explained that the process of forgiveness can take place because of the existence of a meaning that is found in an individual suffering, so as to bring to life meaningful.ÃÂ Keywords: forgiveness, nurturing, parent